Long read sequencing and assembly of wild diploid relatives and cultivars in support of banana breeding programs - Chen, A.; Zhou, X.; Decker, K.; Havecker, E.; Du, E.; Brown, A.; Aitken, E.A.B.; Shah, T.; Uwimana, B.; Hresko, C.; Swennen, R.; Lowdon, R.F. (2024)
Banana is an important fruit and staple crop, which is vital for food and income security in developing countries. A genomics initiative was undertaken as part of the Global Alliance against TR4 (Tropical Race 4 of Fusarium Wilt of Banana) Alliance, with Bayer Crop Science, International Institute of Tropical Agriculture, and University of Queensland to collectively accelerate the breeding efforts in Eastern Africa. The goal of this project is to develop genomics resources to improve banana breeding, productivity, and quality traits amid a changing climate and shifting disease pressures for breeding. Here, we present the PacBio HiFi sequencing, assembly, and comparative analysis of seven genomes of wild and edible diploid banana accessions belonging to subspecies considered important progenitors to cultivated banana varieties and part of breeding programs. This banana genome resource will help power genome editing, a pangenome effort, and conventional breeding programs for germplasm improvement.